Efficiency of scallop Mizuhopecten yessoensis cultivation in the Ussuri Bay (Japan Sea) - Galina S. Gavrilova; Larisa N. Kim (Известия ТИНРО, 2016)
Data on cultivation of scallop Mizuhopecten yessoensis in the Ussuri Bay are generalized. The marine farms are located in the shallow waters at depths of 2-18 m, their plantations occupy different areas with different hydrodynamics. Complex structure of the plantations (collectors, cages and bottom facilities) is formed in the semi-closed Sukhodol Bay, but bottom plantations only for growing of scallop and sea cucumber are mounted in two other bays. The local broodstocks of scallop were formed by juveniles transported from the Posyet Bay, after that at least 20 million individuals of scallop spat were collected in three bays in 2000-2014, and their growing gave the total commercial output about 216 t (111 t in the Sukhodol Bay, 70 t in the Ilmovaya Bay, and 35 t in the Malye Kushi Bay). This is rather weak result that shows that the area has limited abilities for development of this type of aquaculture. The main reason was low density of spat on substrata: it never exceeded 200 ind./collector and did not increase during the farms development, so the farmers were forced to increase the number of collectors to obtain required number of spat; moreover, some years were unfavorable for collecting of juvenile scallops. There is concluded that environmental conditions in the eastern Ussuri Bay are not optimal for the scallop cultivation by extensive method.